Sign changing solutions of a semilinear equation on Heisenberg group - Jianqing Chen (2016)
Here, we studied an elliptic semilinear equation on a non-commutative manifold (the Heisenberg group) with a Dirichlet boundary condition. By using variational methods adapted to this setting, we prove that this problem possesses at least one positive solution and one sign changing solution for some values of the parameters.